Party Factions and Candidate Selection - Bangum, Christine T.; Fiva, Jon H.; Invernizzi, Giovanna M.; Prato, Carlo; Tukiainen, Janne (Germany, 2026)
We study how political parties share power internally by analyzing the allocation of list positions to different factions. We develop a theory of intraparty bargaining in which list positions shape the mobilization efforts of party activists in different factions. Our results allow us to link observable patterns in list allocations to the importance of consensus in intraparty negotiations. We empirically evaluate these predictions using data from Norwegian municipal elections. We exploit a wave of municipal mergers to identify candidates' geography-based factional affiliations. In line with our theory's functionalist logic and consensus-based bargaining, smaller factions are over-compensated in safe list positions. While we also find a slight over-representation in the contested ranks, the relationship between size and resources is much closer to proportionality, as predicted by our theory. Our theoretical and empirical results show that parties can promote consensus among its factions while maintaining mobilization incentives, indicating that equality and efficiency within a political organization can be simultaneously achieved.